Pemberdayaan Ibu PKK Morobakung Melalui Pelatihan Lilin Aromaterapi dari Limbah Minyak Goreng - Tofan, Ali; Reza Rifanda Dwi Candra Maulana; Choiri; Uswatun Khasanah; Nur Mufarokhah (Fakultas Teknik, Universitas PGRI Banyuwangi, 2024)
This community service project conducted by the lecturers and students of STIE NU Trate Gresik in Morobakung Village, Manyar District, Gresik Regency, aimed to empower the local women’s group (PKK) through the utilization of used cooking oil as the raw material for producing aromatherapy candles. The project was initiated due to the lack of awareness and skills among the PKK members in managing used cooking oil, which is often disposed of improperly, causing environmental pollution and health risks. The community service activities were carried out in several strategic stages, including initial awareness-raising sessions, forum group discussions (FGDs), practical demonstrations of candle-making, and packaging design training using the Canva application. The novelty of this program lies in transforming used cooking oil into eco-friendly, high-value aromatherapy candles that align with modern lifestyle trends. After the program's implementation, the PKK members acquired the necessary skills to produce high-quality aromatherapy candles and create appealing packaging designs, which helped them to launch sustainable small-scale businesses. This project also contributed to raising environmental awareness and reducing the negative impact of waste oil on the environment. The results indicated significant improvements in the PKK members' environmental awareness and technical skills, particularly in producing, marketing, and packaging candles. The program has created new business opportunities, improved local economic conditions, and fostered sustainable environmental practices in the community. This community service initiative demonstrates a practical solution to environmental issues while empowering local women to enhance their economic independence.